Advances in Layered Double Hydroxide/Carbon Nanocomposites Containing Ni2+ and Co2+/3+ for Supercapacitors - Kulandaivalu, Shalini; Azman, Nur Hawa Nabilah; Sulaiman, Yusran (Frontiers in Materials, 2020)
The exceptional characteristics and uniqueness of two-dimensional nickel-cobalt layered double hydroxides (Ni-Co LDHs) make them highly desirable material for supercapacitors. A combination of Ni-Co LDHs with carbon-based materials has given stupendous improvement to the performance of supercapacitors in terms of specific energy, specific capacitance, and specific power. Herein, a comprehensive insight into the recent progress of Ni-Co LDHs/carbon composites for supercapacitors is provided to the readers. Beginning with the description on the classification of supercapacitors and the detailed explanation on LDHs and carbon materials. The morphology, properties and electrochemical performances of the Ni-Co LDHs/carbon composites are well-elaborated in this review. The review also discusses the structural identification and important factors that influence the synthesis of LDHs.